Use of different kinds of waste in the construction of new polymer composites: review. (March 2023) - Taurino, R.; Bondioli, F.; Messori, M.
Abstract: Waste valorization is one of the current research areas that has attracted a great deal of attention over the past few years as a potential alternative to the disposal of a wide range of residues in landfill sites. In particular, the development of environmentally friendly and innovative strategies to process several kinds of wastes is an area of increasing importance in our current society. Landfill, incineration, and composting are common, mature technologies for waste disposal. However, they are not satisfactory due to the generation of toxic methane gas and bad odors, high energy consumption, and slow reaction kinetics. The scope of this manuscript is to give a clear overview on the recent development of waste valorization strategies in polymeric matrices for the sustainable production of new polymer matrix composites. In other words, this work should be regarded as a review, providing guidelines for the sustainable development of various industries for the benefit of the society. In fact, the incorporation of waste and/or by-products into polymer composites may represent a new resource and a successful approach to materials suitable for specific applications that promote a circular economy approach. According to this study, there is a considerable amount of research on the application of solid wastes, in particular agricultural wastes, as fillers for thermoplastic and thermoset matrices to obtain composites suitable for application in components subjected to light to moderate loads. As a main drawback, surface pre-treatment is necessary in many cases to increase the adhesion between matrix and fillers and the final mechanical, thermal, and chemical properties of polymer composites. Highlights: Sustainable production of new composite materials (polymer matrix composites). Organic fillers treatment methods to improve the surface interaction. Stakeholders can adopt waste-based composites to spread the concept of sustainability. Locally sourced recycled material as filler can have a positive environmental impact.